Causes of hypercarbia with oxygen therapy in patients with chronic obstructive pulmonary disease - Hanson, 3rd, C W; Marshall, B E; Frasch, H F; Marshall, C (Critical care medicine, 1996)
To compare data derived from a computer model of the pulmonary circulation with data from a case series of patients with chronic obstructive pulmonary disease (COPD). To evaluate the specific factors contributing to CO2 retention due to oxygen therapy in patients with acute exacerbations of COPD. Data from a computer model of the pulmonary circulation were compared with a previous case series. Patient data were derived from previous case series. Simulated application of oxygen therapy. The computer model of the pulmonary circulation generates data comparable with those data from a series of patients with COPD treated with supplemental oxygen and permits identification of the causes for hypercarbia. Therapy with supplemental oxygen alters hypoxic pulmonary vasoconstriction and modulates the Haldane effect, resulting in changes in physiologic deadspace. Changes in physiologic deadspace are sufficient to account for the hypercarbia developed by patients with acute exacerbations of COPD when treated with supplemental oxygen.